Basal cell carcinoma with halo phenomenon in a young female: Significance of dermatoscopy in early diagnosis - Pinar Yuksel Basak; Gonca Meric; Metin Ciris (Wolters Kluwer Medknow Publications, 2015)
Halo phenomenon of nevus may be observed as a circular reaction, although it is unusual around tumors. A 29-year-old woman presented with a pigmented lesion on the cheek since three years. She noted whitening of the skin around the lesion almost after a year following its appearance. Dermatologic examination revealed a pigmented nodular lesion with a hypopigmented halo on the left infraorbital region. The clinical impression was halo nevus, whereas basal cell carcinoma (BCC) was considered in dermatoscopic differential diagnosis. The diagnosis was infiltrative-type BCC histopathologically. The persistence of a perilesional halo around an enlarging pigmented lesion should be carefully examined with accompanying dermatoscopic findings even in young patients for early diagnosis of tumoral lesions.